Fe2O3 nanoparticles anchored on 2D kaolinite with enhanced antibacterial activity. Issue 46 (25th May 2017) - Long, Mei; Zhang, Yi; Shu, Zhan; Tang, Aidong; Ouyang, Jing; Yang, Huaming
Abstract : Fe2 O3 nanoparticles with different dispersion states on the surface of modified kaolinite were controlled for enhancing antibacterial activity. Abstract : An enhanced antibacterial activity of Fe2 O3 nanoparticles was achieved by controlling the distribution density of Fe2 O3 nanoparticles on modified kaolinite nanosheets (Fe2 O3 –KlnKAc ) by adjusting the pH value of the reaction system. A proper distribution density of Fe2 O3 nanoparticles generating higher levels of hydroxyl radicals led to a higher antibacterial activity.